Hadoop Security Challenges and Its Solution Using KNOX - Sirisha N; Kiran K V D; R Karthik (Institute of Advanced Engineering and Science, 2018)
Big Data is a new technology and architecture. It can work on a very large volume of a variety of data with high-velocity, discovery, and/or analysis. Big Data is about the fast-growing sources of data such as web logics, Sensor networks, Social media, Internet text and documents, Internet pages, Search Index data, scientific research. Big data also formally introduces a complex range of analysis. Big data can evaluate mixed data (structured and unstructured) from multiple sources. As there are some security issues in big data which are no longer solved using the hashing techniques on large amount of data, this paper shows an idea of new approach of designing a Knox’ified Hadoop cluster.